National Innovation System and the Development of Scientific and Innovation Policy in the Republic of Armenia - Khnkoyan, A. (Наука та інновації, 2012)
The paper deals with an overview of developments in S&T and innovation sectors in Armenia during the last decade.
Adopted policy documents directed to promote innovation processes and development of national innovation system, and
analysis of the government actions towards addressing the pressing challenge of reformation of S&T and innovation system
in accordance with the requirements of the needs of economic development of the country are presented. Розглянуто розвиток науково-технічного та інноваційного секторів економіки Вірменії за останнє десятиліття.
Представлено державні документи, спрямовані на сприяння інноваціям і розвитку національної інноваційної системи, а також аналіз дій уряду на шляху вирішення нагальних проблем реформування науково-технічної та інноваційної систем Вірменії відповідно до вимог ринкової економіки і потреб економічного розвитку країни. Рассмотрено развитие научно-технического и инновационного секторов экономики Армении за последнее
десятилетие. Представлены государственные документы, направленные на поддержку инновациям и развитию
национальной инновационной системы, а также анализ
действий правительства на пути решения безотлагательных проблем реформирования научно-технической и инновационной систем Армении в соответствии с требованиями рыночной экономики и нужд экономического развития страны.